2003
DOI: 10.1111/j.1949-8594.2003.tb18205.x
|View full text |Cite
|
Sign up to set email alerts
|

An Extended Examination of Preservice Elementary Teachers' Science Teaching Self‐Efficacy

Abstract: The purpose of this study was to examine programmatic factors that positively impact changes in elementary preservice teachers' teaching self‐efficacy beliefs. Specifically, it examined the impact of science methods courses, student teaching, and science content courses on elementary preservice teachers' science teaching self‐efficacy. The Science Teaching Efficacy Belief Instrument Form B was administered, using a pre/post design, to undergraduate elementary education majors in specific education and science … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 15 publications
4
32
0
7
Order By: Relevance
“…According to this result, the self-efficacy belief levels in teaching science of the fourth grade students were higher than the first grade teacher candidates. This result has shown a similarity with the related studies [38,23,24,39,34,7].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to this result, the self-efficacy belief levels in teaching science of the fourth grade students were higher than the first grade teacher candidates. This result has shown a similarity with the related studies [38,23,24,39,34,7].…”
Section: Discussionsupporting
confidence: 92%
“…The judgments of the classroom teachers on the science subject and teaching the sciences [23,24,25] effect of the science teaching main courses on the self-efficacy of the teacher candidates [26,27]. In addition, the studies, which included the self-efficacy perceptions in teaching the sciences of the teacher candidates and the factors playing a role in their attitudes of being a teacher, take place within this literature [24,28,29,30,31,32,33,34]. Teachers with low content knowledge have a higher rate of self-efficacy perception compared to the other teachers, who have a stronger self-efficacy perception of being a teacher.…”
Section: Introductionmentioning
confidence: 99%
“…Research has also found that "the typical experience in college science courses has not fostered meaningful learning in science nor the development of favorable attitudes toward science or science teaching among entering elementary education students" (Briscoe, Peters, & O'Brien, 1993, p. 3). Research by Morrell and Carroll (2003) reported that the nine credits of traditional science courses their students completed resulted in no significant positive change of students' attitudes toward science teaching.…”
Section: Introductionmentioning
confidence: 99%
“…No clear pattern emerges as to the specific nature of these special science courses for elementary teachers, but research into the impact of these courses is beginning to appear. Research by Morrell and Carroll (2003) reports that the new course they examined had no impact on science teaching attitude in preservice teachers. Loucks-Horsley, Schmidt, and Raizen (1989) suggests that exemplary science courses would teach science in an investigative manner emphasizing the central concepts and tools of inquiry unique to the discipline.…”
Section: Introductionmentioning
confidence: 99%
“…Ülkemizde ve yurtdışında öğretmen ve öğretmen adaylarının öz-yeterlik algılarına yönelik çok sayıda araştırma gerçekleştirilmiştir (Altunçekiç, Yaman ve Koray, 2005;Choi, 2005;Çevik, 2011;Demirtaş, Cömert ve Özer, 2011;Ekici, 2008;Friedman, 2003;Friedman ve Kass, 2002;Gençtürk ve Memiş, 2011;Güvenç, 2011;Johnson, Wallece ve Thompson, 1999;Henson, 2002;Kiremit, 2006;Morell ve Caroll, 2003;Morgil, Seçken ve Yücel, 2004;Özkan, Tekkaya ve Çakıroğlu, 2002;Posnanski, 2002;Saracaloğlu ve Dinçer, 2009;Saracaloğlu ve Yenice, 2009;Şahin Taşkın ve Hacıömeroğlu, 2010;Tschannen-Moran ve Hoy, 2001). Sugawara, Thanitthar, Burt, (1998) Akademik kontrol odağı ile ilgili alan yazın incelendiğinde öğretmen ve öğretmen adaylarının akademik kontrol odaklarının çeşitli değişkenlerle olan ilişkisinin incelendiği çalışmalar bulunmaktadır (Agne, 1992;Başol ve Türkoğlu, 2009;Coleman, 1966;Cengil, 2004;Cheng, 1994;Dilmaç, 2008;Durna ve Şentürk, 2012;Elfström ve Kreuter, 2006;Gore ve Rotter, 1963;Hsieh ve Dwyer, 2009;Küçükkaragöz, 1998;Lefcourt, 1982;Nord, Conelly ve Daignault, 2007;Nordstrom ve Segrist, 2009;Martin ve Baldwin, 1993;…”
Section: Fen Bilgisi Sosyal Bilgiler Ve Sınıf öğRetmeni Adaylarının unclassified